Empowering Communities Through GeoGebra: A Training Program on Visualization Technology for Transformation Geometry - Pratama, David; Noverli, Muthiah Fildzah (Jurnal Pengabdian kepada Masyarakat (Indonesian Journal of Community Engagement), 2025)
The integration of technology in mathematics education has garnered increasing attention for its potential to enhance students’ understanding of abstract concepts. This study examined the implementation of a GeoGebra-based training program for pre-service mathematics teachers at Universitas Singaperbangsa Karawang (UNSIKA), focusing on improving their visualization skills in transformation geometry. The training employed a project-based learning approach, incorporating online instruction, group projects, and collaborative discussions. Results indicated that GeoGebra effectively strengthened participants’ conceptual grasp of geometric transformations, as evidenced by high project completion rates and positive survey feedback. Recorded instructional videos significantly supported self-paced learning, with 84.4% of participants utilizing these resources for project completion. However, challenges in comprehending coordinate transformations suggested a need for further guidance and targeted exercises. The study underscored GeoGebra’s efficacy in advancing mathematical visualization skills and advocated for its wider adoption in mathematics teacher education. Future research should investigate extended training durations and adaptive learning strategies to address conceptual difficulties more thoroughly.